Provision Of Additional Food As An Effort To Handling Stunting In Children In Siwalankerto District Surabaya - Hubaedah, Annah; Andarwulan, Setiana (Basic and Applied Nursing Research Journal, 2020)
Stunting (dwarf) is a condition where toddlers have a length or height that is less than age. This condition is measured by size or size which is more than minus two median, standard deviations of the child growth standard of the WHO. Stunting toddlers include chronic nutrition problems caused by many factors such as socio-economic conditions, maternal nutrition during pregnancy, pain in infants, and lack of nutritional intake in infants. The type of research use is pre – experimental with one group design pretest posttest design where the design is no control group. The population of this studi were children who ages under 59 month. Technique samping uses probability sampling with purposive sampling method. Weight measurements were carried out before and after the supplementary food intervention, during the supplementary food intervention and keeping in mind the energy and protein consumption of food other than the supplementary food. he results showed that changes in weight status of children under five according to age indicated that there was a change in weight status of children, namely 2 children became malnourished and 13 others were still in the category of acute malnutrition. The results showed that there were differences in the Weight for Age (WAZ) index status before and after complementary foods.